The German statutory minimum wage and its effects on regional employment and unemployment - Holger Bonin; Ingo Eduard Isphording; Annabelle Krause-Pilatus; Andreas Lichter; Nico Pestel; Ulf Rinne (Institute of Labor Economics (IZA), 2019)
This paper studies the effects of the introduction of Germany's statutory minimum wage in 2015 on employment and unemployment on the level of regional labor markets. Using variation in the regional exposure to the new wage floor, we employ a difference-in-differences approach that compares the evolution of employment and unemployment between regions with varying minimum wage bites. Overall, we find no statistically significant effect of the introduction of the German minimum wage on regular employment subject to social insurance, but a statistically significant negative effect on marginal employment. The reduction is not accompanied by a proportional increase in unemployment.
Keywords: J21; J31; J38; 330; minimum wage; employment; unemployment; labor market regions; Germany